5(y+2)=-3(5y-4)+8y

Simple and best practice solution for 5(y+2)=-3(5y-4)+8y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+2)=-3(5y-4)+8y equation:



5(y+2)=-3(5y-4)+8y
We move all terms to the left:
5(y+2)-(-3(5y-4)+8y)=0
We multiply parentheses
5y-(-3(5y-4)+8y)+10=0
We calculate terms in parentheses: -(-3(5y-4)+8y), so:
-3(5y-4)+8y
We add all the numbers together, and all the variables
8y-3(5y-4)
We multiply parentheses
8y-15y+12
We add all the numbers together, and all the variables
-7y+12
Back to the equation:
-(-7y+12)
We get rid of parentheses
5y+7y-12+10=0
We add all the numbers together, and all the variables
12y-2=0
We move all terms containing y to the left, all other terms to the right
12y=2
y=2/12
y=1/6

See similar equations:

| -2(-3n+9)=-72 | | 5+44=2+r5+44=2+r. | | 11=6x=5(22x+17)-x | | 6(2x/3)=2(4x/7) | | 75+x/5=35 | | 5w+3=w-9 | | -2+4x=5(20x+22)-x | | 5x^2-12=166 | | 5=y/2.56+3 | | 2(x^2+4)=12 | | -4(y+3)=-4 | | 2(x+5)-(x-2)=-3(x-3) | | -4(w+9)=-6w-32 | | 3/7=n/4.2 | | -14+3x=3(8x+10)+x | | 2(x×2+4)=12 | | -3x+23.4=4.2 | | 5x+60-20x=-8-7 | | -2(3x-10)+8x=7x+20+7x | | 2(x•2+4)=12 | | 4b-4=6b+8 | | 5+u/8=-5.24 | | 11x+55^2=0 | | 2x+×/2=15 | | 2(x÷2+4)=12 | | -7v+5(v+6)=28 | | -12.2=5.3+w/7 | | 2-(x+5)-(x-2)=-3(x-3) | | 4+14=x+5 | | 5x-11=11x-33 | | 4y+6=(12.5)2.5 | | 2(x+2+4)=12 |

Equations solver categories